High blood viscosity is associated with high pulse wave velocity in African sickle cell trait carriers - Valentin, Ouédraogo; Mor, Diaw; Ghislain, Lounbano-Voumbi; Khadir, Sow Abdou; Jean Florent, Tiendrebeogo Arnaud; Abdoulaye, Samb; Magid, Hallab; Georges, Leftheriotis; Abdoulaye, Ba (International Journal of Research in Medical Sciences, 2016)
Background: Sickle cell trait (SCT) is the benign condition of sickle cell disease. Often asymptomatic, the SCT carriers have hemorheological disturbances such as blood hyper-viscosity compared to healthy subjects. These disturbances could lead to structural and functional changes in large vessels. The aim of the study was to evaluate the association between blood viscosity (ηb) and pulse wave velocity (PWV) in SCT carriers. Methods: Thirteen SCT with high blood viscosity (SCT_hηb) aged 34±12 years (4 men) were compared to 13 SCT with low blood viscosity (SCT_lηb) aged 32±9 years (5 men) recruited from the National Blood Transfusion Center (CNTS) in Dakar (Senegal). Pulse wave velocity finger-toe (PWVft) was assessed using pOpmètre® (Axelife SAS-France). Cardiovascular risk (CVR) was assessed according to the Framingham Laurier score. Results: SCT_hηb had higher PWVft (m/s) than SCT_lηb respectively 8.98±1.98 and 7.11±1.18 (p = 0.004). CVR score (%) was higher in SCT_hηb than SCT_lηb, but this difference was not statistically significant (5.96±7.45 vs 2.09±2.15; p=0.31). Multivariate linear regression showed a positive correlation between PWVft and ηb and CVR score (r2=0.74, F=21.19, p˂0.001). Conclusions: Present results indicate that the SCT_hηb carriers have arteries stiffer than SCT_lηb and ηb and CVR could remain independent determinants of arterial stiffness in SCT carriers.